DAB vs DAB+ Radio Broadcasting: a Subjective Comparative Study - GILSKI, Przemyslaw (Archives of Acoustics, 2017)
In the age of digital media, delivering high quality content to consumers is one of the most demanding tasks. There exist numerous broadcasting standards, with different pros and cons, and the DAB/DAB+ (Digital Audio Broadcasting) system is one of the most popular among them. From an engineer’s perspective, efficient resource management under limited bandwidth conditions has always been a challenge. In this paper a subjective quality assessment study of the DAB and DAB+ broadcasting system is performed on a representative group of signal samples. It describes the radio link, including a fully functional transmitter designed for the purpose of this test, as well as the receiver side representing a commercially available consumer device, for a truly real-time and end-to-end quality evaluation.